2021
DOI: 10.4103/ijmr.ijmr_3185_20
|View full text |Cite
|
Sign up to set email alerts
|

Non-communicable diseases care during COVID-19 pandemic

Abstract: Background & objectives : During any public health emergency, a need-based national non-communicable diseases (NCD) preparedness plan is essential. People living with NCDs could face challenges owing to restricted mobility, low access to medical care and suboptimal logistics during the pandemic. The present study explored the effect of the COVID-19 pandemic on NCD care in a district of Odisha State of India. Methods : This study was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In our study, we found that PLNCDs across socio-economic strata faced significant challenges when they tried to physically access healthcare, which is similar to findings in other studies from India (11) and elsewhere (16). Uniquely however, we also found that many a times access was restricted due to lack of financial resources, which rendered securing private consultations and procuring medications out of reach (17).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we found that PLNCDs across socio-economic strata faced significant challenges when they tried to physically access healthcare, which is similar to findings in other studies from India (11) and elsewhere (16). Uniquely however, we also found that many a times access was restricted due to lack of financial resources, which rendered securing private consultations and procuring medications out of reach (17).…”
Section: Discussionsupporting
confidence: 90%
“…A rapid survey by WHO assessing NCD access in the wake of COVID-19 pandemic and associated restrictions found that access to outpatient NCD services was interrupted in 59% countries (10). Studies from India (11) and other LMICs have also found decreased utilization of NCD services with the advent of COVID-19 (12,13). However, there is limited information on the impact of COVID-19 on NCD healthcare provision and access from India.…”
Section: Introductionmentioning
confidence: 99%
“…Data collection tools: a pre-tested, structured interviewer-administered questionnaire was used for data collection which contained three parts including socio-demographic characteristics, clinical and treatment related characteristics and were used to assess the perceived impact of COVID-19 on routine care which was adapted and modified from different literature [ 3 - 6 ]. Perceived impact of COVID-19 was measured by 5-items [ 7 ] and each item score was summed up and finally described as described in Table 3 . The instrument was translated to the Afaan Oromo and Amharic versions by experts who were fluent in both languages and back translated to English for consistency.…”
Section: Methodsmentioning
confidence: 99%
“…Perceived impact of COVID-19: was measured by 5-items [ 7 ] and each item score was summed up and finally described as described in the Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The onset of the COVID-19 pandemic has diverted the focus of health systems towards containing the spread of infection, thus concomitantly resulting in disruptions in health services delivery for chronic diseases to a large extent. Our community-based studies on the management of non-communicable diseases (NCD) during COVID-19 lockdown have revealed that people of higher age, having mental illness had significantly more significant care challenges (Pati et al, 2020b;Sahoo et al, 2020). The presence of dementia and the impact of the COVID-19 pandemic pose considerable concerns for the elderly.…”
Section: Introductionmentioning
confidence: 99%